Spionidae (Annelida) from shallow waters around the British Islands: an identification guide for the NMBAQC Scheme with an overview of spionid morphology and biology - Radashevsky, Vasily I. (Zootaxa, 2012)
This is the third guide in a series aimed to help in the identification of northern European samples through the NationalMarine Biological Analytical Quality Control (NMBAQC) Scheme. A review is presented of general morphology andbiology of one of the most common groups in marine and estuarine communities worldwide, spionid polychaetes(Annelida: Spionidae). An identification key to 20 genera and a list of 80 species likely to occur in waters around Britainand Ireland are provided based on the taxonomic literature, collection records and the author’s examination of various collections. The names are updated but some records need verification.